Effect of copper based filler composition on the strength of brazed joint - A. J. S., Hanifah; W. N. W. M. N., Hissyam; Aiman, M. H.; M., Ishak; T., Ariga (Penerbit UMP, 2019)
Vacuum brazing of copper-based filler was performed using pure copper plate as its based metal. The brazed joint was obtained at different temperatures, 680oC and 730oC, with same holding time, which is 30 minutes. MBF 2005 (Cu, 5.7wt.%Ni, 9.7wt.%Sn, 7.0wt.%P), MBF 2002 (Cu, 9.9wt.%Ni, 4.0wt.%Sn, 7.8wt.%P) and VZ 2250 (Cu, 7.0wt.%Ni, 9.3wt.%Sn, 6.3wt.%P) alloys were used as brazing filler materials. The intermetallic compound (IMC) and mechanical properties of the joints were investigated in detail. The result show that the interfacial microstructure of the brazed joints is Cu3P and (CuNi)2P. As the brazing temperature increase from 680oC to 730oC, the IMC become thicker leading to decrease in joining strength due to brittle IMC formation. The maximum shear strength reached 112 MPa at 680oC for MBF 2002 and 129 MPa at 730oC for MBF 2005. Hence, it is found that the composition of filler effects the strength of brazed joint.